Waning Immunity Against Respiratory Syncytial Virus During the Coronavirus Disease 2019 Pandemic. (7th May 2022) - Reicherz, Frederic; Xu, Rui Yang; Abu-Raya, Bahaa; Majdoubi, Abdelilah; Michalski, Christina; Golding, Liam; Stojic, Aleksandra; Vineta, Marina; Granoski, Madison; Cieslak, Zenon; Chacko, Anil; Desai, Neil; et al.
Abstract: Health jurisdictions have seen a near-disappearance of respiratory syncytial virus (RSV) during the first year of the coronavirus disease 2019 (COVID-19) pandemic. Over this corresponding period, we report a reduction in RSV antibody levels and live virus neutralization in sera from women of childbearing age and infants between May to June 2020 and February to June 2021, in British Columbia (BC), Canada. This supports that antibody immunity against RSV is relatively short-lived and that maintaining optimal antibody levels in infants requires repeated maternal viral exposure. Waning immunity may explain the interseasonal resurgence of RSV cases observed in BC and other countries. Abstract : This article shows decreased serum RSV antibody neutralization in women of childbearing age and infants in the context of COVID-19-related social distancing measures, which may have explained the atypical, off-season resurgence of RSV cases in other areas of the world.